Philosophy in the classroom - Lipman, Matthew; Sharp, Ann Margaret; Oscanyan, Frederick S. (Philadelphia : Temple University Press, 1980)
The need for educational redesign. Thinking and the school curriculum. Philosophy. Some educational presuppositions of philosophy for children. The philosophy for children curriculum. Teachingmethodology. Guiding a philosophical discussion. Encouraging children to be logical...
Keywords: United States; Philosophy; Philosophy -- Study and teaching (Primary) -- United States